Working with rock art : recording, presenting and understanding rock art using Indigenous knowledge - Smith, Benjamin, 1969-; Helskog, Knut Arne, 1944-; Morris, David, 1957- (RARI monograph ;, 2012)
This volume contains cutting edge contributions that consider new approaches to three areas: the documentation of rock art; its interpretation using Indigenous knowledge; and the presentation of rock art. Working with Rock Art is the first edited volume to consider each of these areas in a theoretical rather than a technical fashion, and it therefore makes a significant contribution to the discipline. The volume aims to promote the sharing of new experiences between leading researchers in the field. While the geographic focus is truly global, there is a dominant north-south axis with strong representation from researchers in southern Africa and northern Europe, two leading centres for new approaches in rock art research. Working with Rock Art opens up a long overdue dialogue about shared experiences between these two centres, and a number of the chapters are the first published results of new collaborative research--Internet.